ARDESIA-16: a 16-channel SDD-based spectrometer for energy dispersive X-ray fluorescence spectroscopy. (28th July 2021) - Utica, G.; Fabbrica, E.; Carminati, M.; Borghi, G.; Zorzi, N.; Ficorella, F.; Picciotto, A.; Allegretta, I.; Falkenberg, G.; Fiorini, C.
Abstract: We present ARDESIA-16, an X-ray spectrometer based on a monolithic 16-element Silicon Drift Detector (SDD) matrix specifically designed for synchrotron applications. In this work, we describe the main design guidelines which we followed concerning the signal throughput, the energy efficiency, the energy resolution and the overall solid angle covered by detector elements. The characterization of the spectrometer has been made both with radioactive sources in a laboratory environment and with synchrotron light at the P06 beamline (DESY, Hamburg). Experimental results showed an average energy resolution at the optimum peaking time equal to 125 eV (FWHM at Mn Kα), a maximum achieved Output Count Rate (OCR) equal to 17 Mcps, an increase of the energy efficiency above 10 keV thanks to the 1 mm-thick SDD and an overall solid angle equal to 0.4 sr. Finally, we report the first X-ray fluorescence microscopy (XFM) images acquired with an ARDESIA spectrometer.